Poaceae Chloroplast Genome Sequencing: Great Leap Forward in Recent Ten Years - Hu, Yiyu; Sun, Yanqing; Zhu, Qian-Hao; Fan, Longjiang; Li, Jianhua (Current Genomics, 2022)
The first complete chloroplast genome of rice (Oryza sativa) was published in 1989, ushering in a new era of studies of chloroplast genomics in Poaceae. Progresses in Next-Generation Sequencing (NGS) and Third-Generation Sequencing (TGS) technologiesand in the development of genome assembly software, have significantly advanced chloroplast genomics research. Poaceae is one of the most targeted families in chloroplast genome research because of its agricultural, ecological, and economic importance. Over the last 30 years, 2,050 complete chloroplast genome sequences from 40 tribes and 282 genera have been generated, most (97%) of them in the recent ten years. The wealth of data provides the groundwork for studies on species evolution, phylogeny, genetic transformation, and other aspects of Poaceae chloroplast genomes. As a result, we have gained a deeper understanding of the properties of Poaceae chloroplast genomes. Here, we summarize the achievements of the studies of the Poaceae chloroplast genomes and envision the challenges for moving the area ahead.
Keywords: sequencing history